Implementation of the education for sustainable development (ESD) based predict, observe, and explain (POE) learning module to improve critical thinking skills - Fahrun Nisa Umi Fatimah; Joko Siswanto; Harto Nuroso; Muhammad Syaipul Hayat (HAFECS PRESS, 2023)
The learning model is needed so that students are actively involved in exploring and applying material concepts well. One is the POE (Predict-Observe-Explain) model, which can be used in the physics learning process, such as understanding concepts and their application in life. This study aims to test the effectiveness and determine the quality level of an ESD-based POE learning module. This study used a quantitative approach with a pre-experimental method through a one-group pretest-posttest design. The research occurred at SMK Muhammadiyah Lasem, and the sample was class X students. The instruments used were validation sheets and test sheets (posttest-pretest). The quality of the module is determined based on the categorization of validity, while the effectiveness is analyzed through the N-gain statistical test of critical thinking skills from the results of the pretest and posttest. According to material and media experts, the developed ESD-based POE module was very valid. The critical thinking skills demonstrated by N-gain also experienced a significant increase in the experimental class, which was 0.535, compared to the control class, which gained 0.12. The N-gain score of the experiment class is in the high category, and these results indicate that the ESD-based POE learning module effectively involves students actively in learning and applying the concepts they learn. Abstrak. Model pembelajaran diperlukan agar peserta didik terlibat aktif dalam mengeksplorasi dan menerapkan konsep materi dengan baik. Salah satunya yaitu model POE (Predict-Observe-Explain) yang dapat digunakan pada proses belajar fisika seperti memahami konsep-konsep serta penerapannya dalam kehidupan. Penelitian ini memiliki tujuan untuk menguji keefektivan dan mengetahui tingkat kualitas sebuah modul pembelajaran POE berbasis ESD. Penelitian ini menggunakan pendekatan kuantitatif dengan metode pre eksperimental melalui one group pretest posttest design. Penelitian bertempat di SMK Muhammadiyah Lasem dan sampelnya peserta didik kelas X. Instrumen yang digunakan adalah lembar validasi dan lembar tes (posttest-pretest). Kualitas modul ditentukan berdasarkan kategorisasi kevalidan, sedangkan keefektivan dianalisis melalui uji statistic N-gain keterampilan berpikir kritis dari hasil pretest dan posttest. Hasil penelitian menunjukkan modul POE berbasis ESD yang dikembangkan sangat valid baik menurut ahli materi maupun ahli media. Keterampilan berpikir kritis yang ditunjukkan oleh N-gain juga mengalami kenaikan yang signifikan pada kelas eksperimen yaitu 0,535 dibandingkan kelas kontrol yang memperoleh 0,12. Skor N-gain kelas eksperimen tergolong kategori tinggi dan hasil ini menunjukkan bahwa modul pembelajaran POE berbasis ESD efektif untuk melibatkan peserta didik aktif dalam pembelajaran dan menerapkan konsep yang dipelajarinya.